Factors Related to Voluntary Parental Decision-Making in Pediatric Oncology - Miller, Victoria A. (American Academy of Pediatrics, 2012)
OBJECTIVE: The aim of the current study was to examine demographic and contextual correlates of voluntariness in parents making research or treatment decisions for their children with cancer. METHODS: Participants included 184 parents of children with cancer who made a decision about enrolling the child in a research or treatment protocol within the previous 10 days. Parents completed questionnaires that assessed voluntariness, external influence by others, concern that the child’s care would be negatively affected if the parent did not agree, time pressure, information adequacy, and demographics. RESULTS: Lower perceived voluntariness was associated with lower education, male gender, minority status, and not having previous experience with a similar decision. Parents who reported lower voluntariness also perceived more external influence and time pressure, had more concern about the child’s care being negatively affected if they declined, and perceived that they had either too much or not enough information about the decision. In a multivariate regression, education, minority status, gender, external influence, and too little information remained significantly associated with voluntariness. CONCLUSIONS: Several groups of parents appear to be at risk for decreased voluntariness when making research or treatment decisions for their seriously ill children, including fathers, nonwhite parents, and those with less education. Parental voluntariness may be enhanced by helping parents to mitigate the effects of unhelpful or unwanted influences by others and ensuring that their information needs are met.